An Inquisition for Propaganda and Mass Deception: Deposing the Neolithic Mind - Walsh, Robert L. (Frontiers in Communication, 2021)
Human language harbors a mechanical aberration, leaving human communication susceptible to manipulation. Mass deception is the systematic exploitation of this linguistic glitch, the agency of which is premeditated indoctrination. Its influence over human thought and behavior is rooted in the phenomenon of the tribal mind, an unconscious collective ego predisposed to propaganda. In its early modern iterations, it was heralded as a means to establish a shared understanding between an individual and a group that this individual encounters (Bernays, 1928). Any means of communication was seen also a means of propaganda, and this was celebrated. Now, though, inside the utter profusion of multifaceted information, propaganda’s bearing in mass deception cannot be ignored as a contaminant at its source. The challenge is the ease with which communication can be subtly systematized, around an insidious fatal flaw.